Planetary ball milling induced piezocatalysis for dye degradation using BaTiO3 ceramics. Issue 3 (3rd February 2023) - Gaur, Akshay; Chauhan, Vishal Singh; Vaish, Rahul
Abstract : Planetary ball milling assisted piezocatalysis for water cleaning application. Abstract : Piezocatalysis is one of the emerging areas utilized in environmental remediation. The process generally makes use of an ultrasonicator for separating the charges. However, piezocatalysis through an ultrasonicator is just limited to laboratory-scale remediation, and there are various other limitations associated with its usage. Ball milling (BM) is normally utilized for mixing, grinding, and synthesis of precursors. However, BM in the present study is utilized as a piezocatalysis system where a rotating planetary disk and collisions of milling balls generate enough force that abundant reactive species, responsible for the degradation of organic dyes, are produced. For this, methylene blue (MB) dye was used as a pollutant in water with ∼5 mg L −1 concentration and BaTiO3 powder as a piezocatalyst. At 200 rpm, the MB dye degradation was ∼36, ∼61, and ∼54%, respectively, with 5, 10, and 15 Zr balls using 0.15 g of BaTiO3 ceramic powder. The potential of BM as a piezocatalysis system was further analyzed using various parameters ( e.g., speed of BM and the number of milling balls), volume of MB dye, and dose of BaTiO3 ceramic powder.